MSC MALAYSIA APICTA 2013 AWARDS - Universiti Malaysia Sarawak, ISITI-CoERI (Universiti Malaysia Sarawak, (UNIMAS), 2013)
MERIT Best e-Inclusion & e-Community (eTORO: Indigenous Botanical Knowledge Management System of Penans)